Artificial Intelligence-Based Learning Assistance for the Subject of Faith and Morals in Islamic Boarding School-Based Madrasas - Hosna, Rofiatul; Idawati, Khoirotul; Hanifudin; Mahsun, Ali; Budiarti, Erika Mei; Ilahiyah, Iva Inayatul (Communautaire: Journal of Community Service, 2025)
The digital era has brought many significant changes in various aspects of life, including education. Islamic education in Madrasah is required to be more creative, adaptive and responsive, especially in the subject of Moral Faith.  Low digital literacy of teachers and limited infrastructure are obstacles to innovation in the modern era. Therefore, the purpose of this service is to implement artificial intelligence in the form of Canva and Quizizz in learning Akidah Akhlak in order to strengthen the character of students in the Tebuireng Jombang Islamic Boarding School, namely MTs Salafiyah Syafi'iyah and MA Salafiyah Syafi'iyah. The service method used is Participatory Action Research (PAR) which actively involves teachers and students in each stage, starting from problem identification to evaluation. The results of the service showed that the teachers participated in the training well and were filled with high enthusiasm. Using artificial intelligence-based learning media in the form of Canva and Quizizz can increase knowledge, increase creativity, improve skills, make it easier for teachers to deliver material, make it easier for teachers to evaluate learning outcomes through automatic assessment, and improve the quality of madrasah education. The targeted outputs from the results of this service are journals and books.